2021
DOI: 10.1088/1361-6528/ac33d1
|View full text |Cite
|
Sign up to set email alerts
|

Low-dimensional material based wearable sensors

Abstract: Wearable sensors are believed to be the most important part of the Internet of Things. In order to meet the application requirements, low-dimensional materials such as graphene and carbon nanotubes have been attempted to constitute wearable sensors with high performance. Our discussions in this review include the different low-dimensional material based sensors which are employed in wearable applications. Low-dimensional materials based wearable sensors for detecting various physical quantities in surroundings… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 119 publications
0
19
0
Order By: Relevance
“…Whereas, for molecular biology, this is the quickest way of PCR detection by testing the excellent speed μ-scale thermal shift. Due to this, DNA array can be detected more than a million times rapid genome arrangement ( Chakraborty et al, 2018 ; Dwivedi et al, 2021 ; Ho et al, 2021 ; Lei et al, 2019 ; Naguib et al, 2021 ; Novoselov et al, 2004 ; Patel et al, 2016 ; Solanki et al, 2011 ; Wu et al, 2022 ; H. Zhang et al, 2022 ). However, this generation's sensors are unable to incorporate present-day intelligent technological advancements and innovations.…”
Section: Emergence Of 5th Génération Biosensing Strategiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Whereas, for molecular biology, this is the quickest way of PCR detection by testing the excellent speed μ-scale thermal shift. Due to this, DNA array can be detected more than a million times rapid genome arrangement ( Chakraborty et al, 2018 ; Dwivedi et al, 2021 ; Ho et al, 2021 ; Lei et al, 2019 ; Naguib et al, 2021 ; Novoselov et al, 2004 ; Patel et al, 2016 ; Solanki et al, 2011 ; Wu et al, 2022 ; H. Zhang et al, 2022 ). However, this generation's sensors are unable to incorporate present-day intelligent technological advancements and innovations.…”
Section: Emergence Of 5th Génération Biosensing Strategiesmentioning
confidence: 99%
“…The first concern related to 5th generation biosensors is catered by architecting advanced functional nanoplatforms and engineering their physicochemical attributes. Recently, two-dimensional (2D) nanomaterials, including graphene and its derivatives, metal carbides and nitrides (MXenes), metal borides (MBenes), metal-organic framework, metal dichalcogenides and borophene, due to their high specific surface area have emerged as excellent biosensing platforms with enhanced detection and monitoring efficacies ( Ahmed et al, 2020 ; Chakraborty et al, 2018 ; Chaudhary et al, 2022e , 2022a ; Dwivedi et al, 2021 ; Ho et al, 2021 ; Huang et al, 2020 ; Jiang et al, 2020 ; Naguib et al, 2021 ; Wu et al, 2022 ; Zha et al, 2019 ; H. Zhang et al, 2022 ) Amongst all, MXenes have demonstrated enormous potential in detecting and monitoring the diversified biomolecules utilizing various strategies, encompassing electrical, electronic, electrochemical, optical, acoustic and plasmonic modules ( Chaudhary et al, 2022a , 2022c , 2022e ; Sheth et al, 2022 ). It is attributed to the high effective surface area, tunable physicochemical attributes, and rich surface functionalities of MXenes, which contribute to enhanced monitoring performances.…”
Section: State-of-the-art 5th Generation Biosensors: Towards Hospital...mentioning
confidence: 99%
See 1 more Smart Citation
“…[ 12 ] More specifically, CNTs can be employed as conductive fillers for the fabrication of electrically conductive systems, such as sensors, organic capacitors, and transistors. [ 13 ] Their high aspect ratio and high surface area guarantee low percolation concentrations with respect to traditional conductive fillers (such as carbon black and carbon fibers). [ 14 ]…”
Section: Introductionmentioning
confidence: 99%
“…[12] More specifically, CNTs can be employed as conductive fillers for the fabrication of electrically conductive systems, such as sensors, organic capacitors, and transistors. [13] Their high aspect ratio and high surface area guarantee low percolation concentrations with respect to traditional conductive fillers (such as carbon black and carbon fibers). [14] Different acrylic resins filled with CNTs have been investigated due to the possibility to be directly printed through extrusion-based 3D printing and vat photopolymerization processes.…”
Section: Introductionmentioning
confidence: 99%